OPTIMISASI STRUKTUR ALUMINIUM FOAM SANDWICH LANTAI KENDARAAN TEMPUR UNTUK MELINDUNGI PERSONIL DARI BEBAN LEDAK MENGGUNAKAN METODE DESIGN FOR SIX SIGMA (DFSS) - Nur Akbar, Cipta
The security and defense of a nation are important sectors for a state existnance. Therefore, the development in strategic defense equipments is essential especially in the technology improvement. Currently, landmine explosion phenomenon is one of the focuses in defense technology development, such as in the development of Armoured fighting vehicle (AFV) to protect military personnel during operation. The protection of military personnel requires structure enhacement in the AFV design. In terms of protecting the structure from the effects of explosion, knowledge blast response is required such as blast response in the function of various parameters, the response of the structure configuration, and the characteristics of the material. Armoured fighting vehicles are continuously being developed to protect soldiers from landmines. Protection of soldiers in armoured fighting vehicles is carried out by put some add-ons structure on the armoured fighting vehicle floor. The structure being optimize in this research is a sandwich contruction which consists of aluminum foam as a core material covered with two steel plates on both sides. Several designs of sandwich structures were proposed in this study, and the optimum design is selected. Numerical analysis is chosen to simulate several designs potential. As the actual test will be expensive and complex, thus design based on experimental tests was not affordable. Numerical analysis was carried out with non-linear dynamic finite element code, LS-DYNA, where steel plate is modeled as shell element, aluminum foam is modeled as solid element, and concentrated explosive load is modeled with load blast. The numerical simulation results show the responses of the structure in terms of displacement and acceleration. The structure responses are then use in optimization process using the statistical method DFSS (Design For Six Sigma) The optimization results by the DFSS method obtained the optimum design that can reduce the acceleration by 53.68% and displacement by 25.41% from the baseline design. This optimation design process can be used for future armoured fighting vehcle development.